Gender roles in history: women as hunters - Singh, K.S. (2001)
The traditional anthropological view of man as the sole hunter is being questioned today and women's role in hunting is being highlighted. The evidence from India supports the view of women as hunters, no matter how restricted this role may be. The archaeological evidence shows that hunting involved women-men partnerships. Folklore and puranic myths represent mother goddesses as killers of major wild animals. There are many historical examples of queens shooting tigers and panthers. In the colonial period when shooting a tiger became a status symbol, there were sportswomen, both Indian and British, who shot major mammals. Also, women from rural and indigenous communities, with their simple instruments and techniques, killed major mammals to save life and property. A unique tribal hunt that survives as a remnant of women's role as hunters is known as jani shikar, held every 12 years by indigenous women when they go out to hunt wild animals, mainly minor ones today as ideas of conservation seep in. Thus, in spite of general reservations about and prohibitions on women, there is still a role for women in hunting.